Concurrent atrial fibrillation, patent ductus arteriosus and subaortic stenosis in a 3-year Old Newfoundland dog - Kuntz, Jodi (2009)
This case study describes the presenting complaint, history, diagnosis and treatment of atrial fibrillation, patent ductus arteriosus and subaortic stenosis in a 3-year old Newfoundland. The patient’s multiple structural defects provide a unique insight into the outcome of interactions between several sources of hemodynamic pathology. The pathophysiology of each of these defects common diseases will be discussed in detail with special attention to physical exam findings, treatment and prognosis of each condition.